PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PENGGUNAAN KONTEKS DAN MODEL DALAM PMRI - Erna Sari Agusta (ALGORITMA: Journal of Mathematics Education, 2021)
Solving problem solving is difficult for students. Therefore, student-based learning innovations are needed that emphasize the use of contexts and models that can be presented in the form of online learning. This research aims to provide an alternative learning approach that can create student-based learning processes and real-world problems to improve students' mathematical problem-solving abilities. This research uses a qualitative approach with the type of Classroom Action Research (PTK) conducted in three cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. Data analysis refers to the achievement of problem solving indicators. Viewed from the results of the test answers of research subjects through three stages, namely: data reduction, presentation of data, and withdrawal of conclusions. The results showed that the use of context and models serves to bridge students' understanding of concrete mathematics in the real world with abstract mathematics in the form of numbers and number operations to help solve problems. There are an improvements average score of the math problem-solving ability test on the final test of cycle I, II, and III.